2021
DOI: 10.1111/liv.14769
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of cirrhotic cardiomyopathy according to different diagnostic criteria

Abstract: Funding informationDr Marcel Razpotnik received for the cirrhotic cardiomyopathy project a promotional award for young investigators from the Austrian Society of Ultrasonography (Österreichische Gesellschaft für Ultraschall in der Medizin -ÖGUM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 39 publications
1
31
2
2
Order By: Relevance
“…The exact prevalence of CCM in cirrhotic patients remains unclear but recent estimates place it around 60% [27,28]. In our study it was only 15%.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The exact prevalence of CCM in cirrhotic patients remains unclear but recent estimates place it around 60% [27,28]. In our study it was only 15%.…”
Section: Discussioncontrasting
confidence: 63%
“…Since approximately 7%-21% of deaths after liver transplantation result from cardiovascular complications [12], it is possible that the new CCC criteria may be too restrictive to apply to advanced-cirrhotic patients. Another recent publication compared the two diagnostic criteria in 122 patients with cirrhosis [28]. They found that the overall prevalence of cirrhotic cardiomyopathy was similar for the old criteria (67.2%), compared to the new (55.7%, P=0 .9).…”
Section: Discussionmentioning
confidence: 98%
“…A recent study we performed, retrospectively evaluated CCM in 141 liver transplant candidates and found it to affect 34.8%, per the CCMC criteria. 3 However, in the current study, 1 the CCMC criteria yielded a prevalence that is as high as 55.7%. In reviewing the data provided, it appears that the higher prevalence is due to considering patients with GLS >22% as having CCM.…”
Section: Cirrhotic Cardiomyopathy Prevalence According To the New Cricontrasting
confidence: 66%
“…Cirrhotic cardiomyopathy is a clinical syndrome of chronic cardiac dysfunction that occurs in patients with cirrhosis (irrespective of the etiology) with no known cardiac disease and is characterized by high cardiac output at rest and blunted contractility response to stress (whether physiological, pathological, or pharmacologic stress) and/or altered diastolic relaxation with abnormal electrophysiological changes ( 71 ). It is estimated that about 60% of patients with cirrhosis have cirrhotic cardiomyopathy ( 72 ). Proposed redefined criteria were proposed by the Cirrhotic Cardiomyopathy Consortium in 2019 ( Table 2 ) ( 73 ).…”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%